2020
DOI: 10.3390/s20216031
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things and Machine Learning for Healthy Ageing: Identifying the Early Signs of Dementia

Abstract: Identifying the symptoms of the early stages of dementia is a difficult task, particularly for older adults living in residential care. Internet of Things (IoT) and smart environments can assist with the early detection of dementia, by nonintrusive monitoring of the daily activities of the older adults. In this work, we focus on the daily life activities of adults in a smart home setting to discover their potential cognitive anomalies using a public dataset. After analysing the dataset, extracting the features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…While there have been advances in detecting early neuropathology, it may be necessary to consider a shift in the diagnostic paradigm so that milder dementia can be detected earlier in order to obtain greater benefits from interventions [ 22 , 23 ]. Identifying the symptoms of the early stages of dementia is often difficult among older adults living in residential care [ 24 ]. It has been reported that more than 10% of community-dwelling subjects older than 70 years suffer from very mild or mild dementia [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been advances in detecting early neuropathology, it may be necessary to consider a shift in the diagnostic paradigm so that milder dementia can be detected earlier in order to obtain greater benefits from interventions [ 22 , 23 ]. Identifying the symptoms of the early stages of dementia is often difficult among older adults living in residential care [ 24 ]. It has been reported that more than 10% of community-dwelling subjects older than 70 years suffer from very mild or mild dementia [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some researchers used wearable sensors to estimate lower limb muscle strength [9] or evaluated the extent of frailty [10]. In addition, models for detecting danger pose [11] and anomalies of health data [12] were constructed in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Daily activity patterns of people with dementia were analyzed by ML methods based on data recorded via environmental sensors [ 6 , 7 ]. A classification model for dementia was developed by extracting and selecting distinctive features based on the dynamic ranking based on a public dataset of daily life activities of adults in a smart home [ 8 ]. Outcomes for older adults in wearables and artificial intelligence (AI)–powered digital health community was improved [ 9 ].…”
Section: Introductionmentioning
confidence: 99%